Using Songs to Teach English Vocabulary to Young Learners in Kindergarten - Abel Wulandari Kusuma Putri; Katharina Rustipa (research, training and philanthropy institution Natural Aceh, 2023)
From the phenomena around them, young learners find it difficult to learn vocabulary because they are still in e active phase, especially learning English. Therefore, knowing a good and effective way to teach English vocabulary using songs is essential. This study aims to determine the use of songs to teach English vocabulary by teachers at TK 'Aisyiyah Bustanul Athfal (ABA) 51. To be able to answer research questions, researchers conducted classroom observations and interviews with teachers who teach English in class. The subjects of this study were class B students, namely classes B1, B2, and B3. From the observations and interviews that researchers have conducted, it is known that teachers have taught well according to the correct stages and enabled children to recognize vocabulary well at each meeting. Students have high learning enthusiasm when the teacher teaches vocabulary using songs that are shown by being active students. The study results show that songs are very effective for teaching English vocabulary to students because they can foster learning motivation so that students can easily remember the vocabulary being taught and that the objectives of teaching vocabulary are well achieved.